2021
DOI: 10.1016/j.amsu.2021.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Students and faculty perception of distance medical education outcomes in resource-constrained system during COVID-19 pandemic. A cross-sectional study

Abstract: Introduction The COVID-19 pandemic has imposed significant challenges on medical education worldwide, particularly in experience- and resource-limited regions of the world. Collaborative efforts of educators and academic institutions are necessary to facilitate the adaptation to the new educational reality. In this study, challenges and outcomes of a newly implemented distance education curriculum are examined to share findings and provide recommendations. Methods An al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 11 publications
9
80
0
3
Order By: Relevance
“…varies for situations. Tuma et al [14], an example of the studies conducted to [18], Gismalla et al [19] also applied a questionnaire to evaluate the perceptions of medical students about distance education. There are also studies in which scales are used instead of questionnaires in the evaluation of the perception of distance education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…varies for situations. Tuma et al [14], an example of the studies conducted to [18], Gismalla et al [19] also applied a questionnaire to evaluate the perceptions of medical students about distance education. There are also studies in which scales are used instead of questionnaires in the evaluation of the perception of distance education.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies examine the perceptions of distance education according to the graduate/undergraduate students, lecturer/instructor, department/faculty/institution, courses and different countries where they study [6][7][8][9][10][11][12][13]. A large number of different studies have been conducted in which a questionnaire was applied to measure the perception of distance education among medical students [14][15][16][17][18][19]. In addition to studies using questionnaires in the evaluation of the perception of distance education, some studies develop and use scales [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Whether we will ultimately embrace online teaching, remains to be seen and is likely also dependent on whether audibility and strength of internet connections. A recent survey among students and teachers in Iraq, reported increased difficulties due to COVID-19 enforced online learning among 69% of students and 51% of teachers (Tuma et al, 2021). Also in the United States, a nationwide survey among pharmacology students revealed that only 30% of the students preferred blended approaches, whereas 47% explicitly wants to return to normal classes (Hamilton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed studies indicated that technological barriers (e.g., software and hardware), weak servers without the capacity for high user volume, and systems with poor visual communication with the audience adversely affect online learning. Unreliable internet service, internet connection, internet costs and financial support issues, frequent power outages (power fluctuation), and network issues (poor bandwidth) were among the other challenges identified in the previous studies in this regard (10,12,13,(15)(16)(17)(18)(19)(20).…”
Section: Structural Challengesmentioning
confidence: 97%